To engage with the Left... From a Profession? The political radicalization of Social Work since the contributions from Helio Gallardo - Villegas Herrera, César (2025)
Latin American Social Work is a profession that shows a marked and constant tendency to radicalize towards the political left. This paper analyzes the historical development of this process based on Helio Gallardo’s theoretical contributions, focusingon its scope, limitations, as well as on the ideological deformations resulting from the link that universities tend to establish with popular struggles.